Loneliness and social engagement in older adults based in Lombardy during COVID‐19 lockdown: The long‐term effects of social networking sites training course: Developing topics - Rolandi, Elena (Alzheimers Dement, 2020)
BACKGROUND: Older people are at greater risk of infection and mortality from COVID‐19 and 52.3% of the deceased in Italy are Lombardy’s residents. Moreover, lockdown measurements may disproportionately affect elderly, since they are less familiar with communication technology used to overcome the lack of in person social contacts. The present study aimed at exploring how older adults residing in Lombardy are experiencing the lockdown period, in relation to loneliness, social isolation and use of communication technology. METHOD: In the first two weeks of May (2020) a telephone interview was conducted with people aged between 81 and 85, residing in the community, who participated in a study aimed at evaluating the impact of Social Networking Sites (SNS) use and older people’s social relationship (clinicaltrials.gov: NCT04242628). We collected information on SNS use, self‐perceived loneliness (UCLA scale 3‐item), social engagement with family and friends (Lubben Social Network Scale 6‐item). Among the eligible individuals (N=144), 1 deceased, 4 refused and 9 were unreachable, resulting in a sample of 130 interviewed. For the aim of the present investigation, participants were stratified as trained (N=60) and untrained (N=70) for SNS use, based on their attendance to group courses held last year as part of the main experimental study. RESULT: Trained and untrained participants were comparable for age, sex, education, percentage of living alone, global cognition, depressive symptoms and comorbidity (Table 1). Participants trained for SNS use reported significantly higher usage of Facebook and WhatsApp and reduced feeling of being left out during the COVID‐19 lockdown (Table 2). Moreover, a trend toward significance was found for an inverse relationship between WhatsApp usage frequency and feeling of lack of companionship (r(s) = ‐0.257, p = 0.051; Table 3). CONCLUSION: Though SNS are unable to completely replace in person contact, these preliminary results support the utility to train older adults for SNS use in order to improve their social inclusion, even in extreme conditions of self‐isolation and vulnerability due to COVID‐19 pandemic.